Subjective indicators of fatigue in football - Effects of fatigue status and subject identity - Noor, D.; Hecksteden, A.; Howle, K.; Duffield, R.; Skorski, S.; Meyer, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Current athlete monitoring approaches in many sport settings use a mix of subjective and objective indicators of fatigue. Whilst, there is recent evidence to suggest subjective measures reflect training load with greater sensitivity and consistency than objective measures (1,2), the appropriateness of a fatigue indicator will ultimately be determined by its long-term diagnostic accuracy, along with its potential sources of variability and bias. Thus, this study aims to analyse the inter- and intra-individual variability of football players` subjective ratings of wellness during the seasonal competition phase. Methods: 35 male football players (1st League Australia, 25.3 ± 4.8 y) participated in the study. Individual perceptual ratings of wellness (fatigue (F), sleep quality (SQ), muscle soreness (MS), stress (S) and mood (M)) were repeatedly collected during the competition phase of a football season using a previously published questionnaire (3). Individual`s ratings were retrospectively classified into `fatigued` and `recovered` states according to recent physical load. Players were defined as fatigued after performing >30 match-day minutes and as recovered when they had >1 post-match rest/recovery day. A minimum of 6 observations per fatigue and subsequent recovery status was necessary to be included for analysis (n=14). Variability was then analysed using a mixed effects model (fixed factor: fatigue status, random factor: subject ID and fatigue status-by-subject ID interaction). Results: The fixed effect of fatigue status was highly significant for all fatigue parameters (p < 0.001). The proportion of total variability attributable to fatigue status-by-subject ID was: W (40.7%), F (34.2%), SQ (19.4%), MS (21.8%), S (18.5%), and M (17.6%). between-subject variabitity (random effect subject ID) was calculated to be redundant for F, SQ and W and very small for M (4.6%) and S (9.1%). Discussion: The current study indicates that fatigue status-by-subject ID interaction (`individual response`) explains a substantial proportion of variability in subjective ratings of fatigue in elite football players. By contrast, between-subject variability in fatigued and recovered ratings was small. Thus, when longitudinally examining the fatigue status of a footballer it is relevant to consider inter-individual differences in the magnitude of fatigue induced changes in ratings of subjective wellness.